Zalan Liu Deng Tao fandong luxian / compiled by The Beijing workers, peasants, soldier physical-education institute/The Mao Zedong Thought corps/The revolutionary committee propaganda group. . Smash the reactionary road of Liu Deng and Tao to a pulp ([s.n.], 1967)
Cartoons. See also BRO 5912/7.